Distribuição tecidual, neuroproteção e efeitos anti-inflamatórios do conjugado LDE/metotrexato após isquemia cortical induzida por microinjeções de endotelina 1 em ratos adultos - PEREIRA, Edmundo Luís Rodrigues (Universidade Federal do Pará, 2018)
Ischemic stroke is one of the leading causes of morbidity and mortality in adults worldwide. Currently, there is only a single pharmacological therapy available to treat such neural disorder, using a high-cost thrombolytic agent, which must be administered within 4 hours of the onset of symptoms, but with a significant risk of transforming the initially oligoemic area into a catastrophic cerebral haemorrhage. In the last decades, nanoparticles with high affinity for certain types of tissues and specially configured with an enhanced diffusibility through biological barriers, have been employed as vehicles to carry therapeutic agents. Among these, the novel liposomal nanoparticle LDE conjugated to the agent methotrexate (cLDE / MTX) has been successfully tested in several experimental models of inflammation, with promising results. Considering that modulation of the inflammatory process that accompanies cerebral infarction is of prognostic significance, the present study investigated the effects of cLDE / MTX upon an experimental model of cerebral ischemia induced by the vasoconstrictor agent endothelin-1 (ET-1) in the cerebral cortex of adults rats. During the first phase of the study, the behavior of tritiated LDE particles (LDE3H+) concerning the blood-brain barrier (BBB), once injected through the caudal vein, was evaluated in either sham animals (N = 18) and animals submited to ET-1 injection (80pMol / Μl) directly into the frontal cortex (N = 5). Further, the anti-inflammatory and neuroprotective effects of cLDE / MTX (1 mg / kg), also injected by caudal vein, were investigated in ischemic animals (N = 5), with the control group (N = 5) receiving only free LDE. All animals were perfused with 0.9% saline and 4% paraformaldehyde 7 days after ischemic induction. Histopathological findings were evaluated by staining with cresyl violet and immunohistochemistry for adult neuronal bodies (anti-NeuN), astrocytes (anti-GFAP) and microglia (anti-Iba1). The results showed that LDE3H+ positively crosses BBB in both sham animals and ischemic animals, and that cLDE / MTX treatment, despite the fact that it reduces not the total area of primary infarction, was able to considerably reduces microglial activation phenomenon at the center of the lesion, inducing as well a significant neuronal preservation at the periphery of the infarction, when compared to the control animals, injected only with unconjugated LDE (P <0.01). At last, the astrocytosis phenomena usually encountered in cerebral ischemia remained unchanged. The results indicate that cLDE / MTX is a promising anti-inflammatory and neuroprotective agent in such experimental model of ischemic stroke. Future studies are desirable in order to increase knowledge about these outcomes, including in animal models with longer survivals.